Pewna Klasa Rozwiązań Zagadnienia Trójwymiarowego dla Materiału Sztywno-Idealnie Plastycznego z Rodziną Chwilowo Nierozciągliwych Płaszczyzn - Gambin, W. (Engineering Transactions, 1972)
In the paper given is the set of solutions for a rigid-perfectly plastic material with a threeorthogonal system of three families of surfaces, one of which represents a family of planes. The solutions form a natural generalization ( to a three-dimensional case) of the results concerning plane orthogonal slip-line lattices with a family of straight lines. The set of solutions presented form the following three classes of resu1ts: 1) generalized torsion of prismatic rods; 2) generalized torsion of rods with variable circular cross-section; 3) the class of solutions derived in [1].